rectracted - Estika Satriani; Afrizal Afrizal (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Intentional academic misconduct: Simultaneous submissions to multiple  journals, conflicts of interest, fabrication or manipulation of data, failure to comply with research protocols, plagiarism, or salami slicing